UJI AKTIVITAS EKSTRAK LABU AIR (Lagenaria siceria) TERHADAP LUKA BAKAR TIKUS JANTAN GALUR WISTAR - Holdin Eka Prilia, Rosida (AKADEMI FARMASI JEMBER, 2017)
Water pumpkin (Lagenaria siceria) is a useful plant in Indonesian. People used water pumpkin flesh as a drug wound, especially as wound burning. This study was prove the activity of water pumpkin flesh extract as wound burning in male rats Wistar strain. The method in this research used experimental. This study used 25 male rats Wistar strain divided into 5 groups. The positive control group was given bioplacenton, the negative control group was given CMC-Na base gel, the other group was given water pumpkin gel extract at doses 2.5%, 5% and 7.5%. compount of water pumpkin extract are flavonoid and saponin. This compount have activity as a burn medicine in male rats wistar strain. At activity level 2.5% has activity 40,06%, at dose 5% has activity 49,75%, and at dose 7.5% has activity 60,11%. Water pumpkin gel extract at 2.5%, 5%, 7.5% dose had different activity with negative control group with CMC-Na gel base, but no significant difference (sig 0,05) 25%, 50%, 75%.Keyword : Healing burn medicine, Water Pumpkin, and male rats wistar strain.